Plasmid-Chromosome Crosstalk in Staphylococcus aureus: A Horizontally Acquired Transcription Regulator Controls Polysaccharide Intercellular Adhesin-Mediated Biofilm Formation - Marincola, Gabriella; Jaschkowitz, Greta; Kieninger, Ann-Katrin; Wencker, Freya D.R.; Feßler, Andrea T.; Schwarz, Stefan; Ziebuhr, Wilma (Frontiers in Cellular and Infection Microbiology, 2021)
Livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) of clonal complex CC398 typically carry various antimicrobial resistance genes, many of them located on plasmids. In the bovine LA-MRSA isolate Rd11, we previously identified plasmid pAFS11 in which resistance genes are co-localized with a novel ica-like gene cluster, harboring genes required for polysaccharide intercellular adhesin (PIA)-mediated biofilm formation. The ica genes on pAFS11 were acquired in addition to a pre-existing ica locus on the S. aureus Rd11 chromosomal DNA. Both loci consist of an icaADBC operon and icaR, encoding a corresponding icaADBC repressor. Despite carrying two biofilm gene copies, strain Rd11 did not produce PIA and transformation of pAFS11 into another S. aureus strain even slightly diminished PIA-mediated biofilm formation. By focusing on the molecular background of the biofilm-negative phenotype of pAFS11-carrying S. aureus, we identified the pAFS11-borne ica locus copy as functionally fully active. However, transcription of both plasmid- and core genome-derived icaADBC operons were efficiently suppressed via IcaR. Surprisingly, although being different on the amino acid sequence level, the two IcaR repressor proteins are mutually replaceable and are able to interact with the icaA promoter region of the other copy. We speculate that this regulatory crosstalk causes the biofilm-negative phenotype in S. aureus Rd11. The data shed light on an unexpected regulatory interplay between pre-existing and newly acquired DNA traits in S. aureus. This also raises interesting general questions regarding functional consequences of gene transfer events and their putative implications for the adaptation and evolution of bacterial pathogens.